Threatened birds face new distribution under future climate change on the Qinghai-Tibet Plateau (QTP). (June 2023) - Li, Bin; Liang, Chengbo; Song, Pengfei; Liu, Daoxin; Qin, Wen; Jiang, Feng; Gu, Haifeng; Gao, Hongmei; Zhang, Tongzuo
Graphical abstract: Highlights: Climatically suitable habitats for threatened birds on the QTP are mainly located in the eastern region. Over 81% of the threatened birds would experience reduction of suitable habitat area in the future. Most threatened birds would be distributed towards higher latitudes or higher elevations. Birds in Galliformes order would face higher extinction risk in future climate change. Abstract: The Qinghai-Tibet Plateau (QTP) contains a significant amount of biodiversity which provides a wide range of habitats for a great quantity of wildlife, especially various birds, on account of the unique climatic conditions and geography. However, the QTP has shown more sensitivity and vulnerability to global climate change than other regions, and the change pose a threat to the birds. Here, we used the MaxEnt and the barycenter shift analysis for analyzing the effects of global warming on the potential future habitat of the threatened birds on the QTP by using the ACCESS-ESM1-5 global climate model of the Coupled Model Intercomparison Projects Phase 6 (cmip6) climate pattern with three Shared Socioeconomic Pathway (SSP). The results demonstrated that the climatically suitable habitats for the threatened birds are mainly distributed in the eastern and central regions of the QTP. Moreover, over 81% of the threatened birds would experience a reduction in suitable habitat area within the next 30–50 years in the different future global warming scenario. Satyr tragopan ( Tragopan satyra ) would lose the most habitat (57.15%), while the Tibetan babax ( Pterorhinus koslowi ) would lose the least (0.35%) in comparing to these birds. Nonetheless, some threatened birds showed an increase in their future habitat area because of their physiological characteristics which are more adaptable to a wide range of climate. The climatic suitable habitat for all the threatened birds, except for the Tibetan eared pheasant ( Crossoptilon harmani ), would move to higher altitudes or higher latitudes regions. Simultaneously, the threatened birds in the order of Galliformes had a higher risk of extinction due to their weak flight and extended migratory distances on the QTP in the future. Our study provides provide a data foundation for the conservation of biodiversity and wild birds on the QTP.